Precision Nutrition in Chronic Inflammation - Demetrowitsch, Tobias J.; Schlicht, Kristina; Knappe, Carina; Zimmermann, Johannes; Jensen-Kroll, Julia; Pisarevskaja, Alina; Brix, Fynn; Brandes, Juliane; Geisler, Corinna; Marinos, Georgios; Sommer, Felix; Schulte, Dominik M.; et al. (Frontiers in Immunology, 2020)
The molecular foundation of chronic inflammatory diseases (CIDs) can differ markedly between individuals. As our understanding of the biochemical mechanisms underlying individual disease manifestations and progressions expands, new strategies to adjust treatments to the patient’s characteristics will continue to profoundly transform clinical practice. Nutrition has long been recognised as an important determinant of inflammatory disease phenotypes and treatment response. Yet empirical work demonstrating the therapeutic effectiveness of patient-tailored nutrition remains scarce. This is mainly due to the challenges presented by long-term effects of nutrition, variations in inter-individual gastrointestinal microbiota, the multiplicity of human metabolic pathways potentially affected by food ingredients, nutrition behaviour, and the complexity of food composition. Historically, these challenges have been addressed in both human studies and experimental model laboratory studies primarily by using individual nutrition data collection in tandem with large-scale biomolecular data acquisition (e.g. genomics, metabolomics, etc.). This review highlights recent findings in the field of precision nutrition and their potential implications for the development of personalised treatment strategies for CIDs. It emphasises the importance of computational approaches to integrate nutritional information into multi-omics data analysis and to predict which molecular mechanisms may explain how nutrients intersect with disease pathways. We conclude that recent findings point towards the unexhausted potential of nutrition as part of personalised medicine in chronic inflammation.